ENHANCING LEADERSHIP KNOWLEDGE THROUGH THE MINI MBA FOR SCHOOL LEADERS TRAINING PROGRAM - Syamril; Arohman, Mamat; Palupi, Palupi; Zaeni, Arpan (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2025)
Leadership knowledge is crucial for school leaders to build strong teams and achieve institutional goals. When this foundational knowledge is lacking, progress is often hindered. This study evaluates the effectiveness of the